2008
DOI: 10.1037/0033-2909.134.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Refining the relationship between personality and subjective well-being.

Abstract: Understanding subjective well-being (SWB) has historically been a core human endeavor and presently spans fields from management to mental health. Previous meta-analyses have indicated that personality traits are one of the best predictors. Still, these past results indicate only a moderate relationship, weaker than suggested by several lines of reasoning. This may be because of commensurability, where researchers have grouped together substantively disparate measures in their analyses. In this article, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

177
1,154
20
80

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,429 publications
(1,504 citation statements)
references
References 373 publications
177
1,154
20
80
Order By: Relevance
“…Neuroticism is the personality trait most strongly linked to wellbeing (Boyce et al, 2013;DeNeve & Cooper, 1998;Steel, Schmidt, & Shultz, 2008), and so it is likely that at least temporary changes in neuroticism would have taken place. Such a finding, rather than being inconsistent, helps to illustrate differences between relatively stable predispositions and temporary shifts to well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroticism is the personality trait most strongly linked to wellbeing (Boyce et al, 2013;DeNeve & Cooper, 1998;Steel, Schmidt, & Shultz, 2008), and so it is likely that at least temporary changes in neuroticism would have taken place. Such a finding, rather than being inconsistent, helps to illustrate differences between relatively stable predispositions and temporary shifts to well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative affects are considered two main components of happiness and they are associated to extraversion and neuroticism (low emotional stability) respectively (Pavot & Diener, 2011). Moreover, the metaanalysis of Steel, Schmidt, and Shultz (2008) indicated that extraversion and neuroticism broad domains were the best predictors of subjective wellbeing. In relation to the second outcome, as expected, extraversion and conscientiousness presented positive and negative correlations respectively to alcohol use (Mezquita, Ibáñez, Moya, Villa, & Ortet, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Extraversion is one of five basic trait domains that describe the structure of personality (John, Naumann, & Soto, 2008), and can be defined as the tendency to be talkative, assertive, and sociable at the high end of the continuum, and quiet, passive, and reserved at the opposite ("introverted") end. The tendency for extraverts to experience higher levels of positive affect (PA) is often described as one of the most robust findings in personality psychology (Lucas & Fujita, 2000;Smillie, DeYoung, & Hall, 2015;Steel, Schmidt, & Shultz, 2008), and holds across several cultures (Lucas, Diener, Grob, Suh, & Shao, 2000). This relation is strongest when PA is defined, in line with Watson and Tellegen's (1985) factor model of affect, as the combination of pleasant valence and high activation (e.g., lively, excited; see Smillie, DeYoung, & Hall, 2015).…”
mentioning
confidence: 99%